The Effectiveness of Green Betel Leaf (Piper betle Linn) on Perineal Wound Healing: A Literature Review Study - Devi Endah Saraswati (Universitas Nahdlatul Ulama Surabaya, 2022)
The perineal injury during delivery can increase the risk of infection in postpartummothers. This paper reviews the effectiveness of green betel leaf (Piper betle Linn) onperineal wound healing. It was a literature review study. The first literature review stagewas to determine the problem using PICO questions. Then, search and collectdata/literature with the following steps: write keywords in the journal database andchoose articles according to the specified criteria. The databases were Google Scholar,Science Direct, and Technology Index (SINTA), and PMC. The population was nationaljournals examing the effectiveness of betel leaf on perineal wound healing. In addition,inclusion criteria were national journals researching the effectiveness of betel leaf onperineal wound healing and published from 2015 to 2020. Meanwhile, the exclusioncriteria were journals with no full text. The journal searching was carried out from 1 to20 August 2020. Data analysis used the following methods: critical appraisal, skimming,scanning, separating irrelevant articles from relevant articles, reading relevant articles,and making notes or summaries. Then we arranged publications in the table andanalyzed them. There were seven relevant journals from Google Scholar. The findingsshowed that betel leaf was effective for perineal wound healing. The betel leaf containsan antiseptic five times stronger than ordinary phenol. It also contains saponins thattrigger collagen formation for wound healing. Future researchers should examine thedegree of the perineal wound and explain the processing of betel leaf in detail.